Effects of medical communication curriculum on perceptions of Korean medical school students - Yoo, Hyo Hyun (Korean J Med Educ, 2018)
PURPOSE: The study examines changes in students’ self-assessment of their general communication (GC) and medical communication (MC) competencies, as well as perceptions of MC concepts. METHODS: Participants included 108 second year medical students enrolled at a Korean medical school studying an MC curriculum. It was divided into three sections, and participants responded to questionnaires before and after completing each section. To assess perceived GC and MC competency, items based on a 7-point Likert scale were employed; a single open-ended item was used to examine students’ perceptions of MC. Statistical analysis was conducted to gauge GC and MC competency, whereas semantic network analysis was used to investigate students’ perceptions of MC. RESULTS: Students perceived their GC competency to be higher than MC. Perceived MC competency differed significantly across the three sections, whereas no differences were found for GC. There were no statistically significant differences after completing the curriculum’s second and third sections; however, the vocabulary students used to describe MC concepts became more scholarly and professional. In the semantic networks, the link structure between MC-related words decreased in linearity and looseness, becoming more complex and clustered. The words ‘information’ and ‘transfer’ proved integral to students’ perceptions; likewise, ‘empathy’ and ‘communication’ became closely connected in a single community from two independent communities. CONCLUSION: This study differed from prior research by conducting an in-depth analysis of changes in students’ perceptions of MC, and its findings can be used to guide curriculum development.